Tahfizhul Qur'an Imam Asy-Syatiby High School Students’ Mastery of Fi’il through Studying the Book al-Jāmi’ by Ibnu Ḥajar al-‘Asqalānī (Morfologi Study) - Muslimin, Muslimin; Anwar Abd. Rahman; Amrah Kasim; Sirajuddin, Sirajuddin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
The objective of the study was to determine whether the book al-jāmi study method was successful in facilitating students' mastery of the Arabic language learning material, especially material about fi’il. The present study incorporated field research employing qualitative descriptive analysis. The research utilized a variety of data sources including scholarly literature, interview papers, questionnaires, observations, tests, and other supplementary data sources using a phenomenological approach. The findings of this study revealed a limited degree of proficiency among students in regards to the fi’il or verb form, as assessed through the examination of the al-jāmi textbook. Based on the examination outcomes of a sample including 30 pupils, the scores achieved were distributed as follows: 6.7% in the high category, 26.7% in the medium category, 30% in the low category, and 36.7% in the very low category. Based on the given percentage, one might infer that the kids' proficiency in fi’il falls below the established standard or is notably deficient. This phenomenon can be attributed to a variety of factors. Firstly, the absence of any form of evaluation following the study led to decreased motivation among students. Additionally, insufficient emphasis was placed on the importance of recording the material presented, further contributing to the issue. Secondly, the timing of the study sessions was deemed inappropriate, potentially impacting students' ability to absorb and retain information. Based on the findings of this study, it is imperative for the educational institution to assess the program.